2021
DOI: 10.1177/1528083720984973
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and modeling of thermal protective fabrics under Molotov cocktail exposure

Abstract: This study aims to characterize and model the thermal protective fabrics usually used in workwear under Molotov cocktail exposure. Physical properties of the fabrics were measured; and, thermal protective performances of the fabrics were evaluated under a fire exposure generated from the laboratory-simulated Molotov cocktail. The performance was calculated in terms of the amount of thermal energy transmitted through the fabrics; additionally, the time required to generate a second-degree burn on wearers’ bodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…This is because a fabric with high air permeability could transfer more steam through the porous surface of the fabrics and that could lower the performance of the fabrics. In a recent study, Mandal et al (2021) [ 99 ] investigated the impact of wide range of fabric properties on the performance under steam exposure. It has been found that thickness, air permeability and evaporative resistance of the fabrics are three most significant properties to affect the performance.…”
Section: Characterization and Modeling Of Thermal Protective Performance Of Polymeric Textile Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because a fabric with high air permeability could transfer more steam through the porous surface of the fabrics and that could lower the performance of the fabrics. In a recent study, Mandal et al (2021) [ 99 ] investigated the impact of wide range of fabric properties on the performance under steam exposure. It has been found that thickness, air permeability and evaporative resistance of the fabrics are three most significant properties to affect the performance.…”
Section: Characterization and Modeling Of Thermal Protective Performance Of Polymeric Textile Materialsmentioning
confidence: 99%
“…It has been found that thickness, air permeability and evaporative resistance of the fabrics are three most significant properties to affect the performance. By employing these properties, Mandal et al (2021) [ 99 ] also developed the MLR and ANN model to predict the performance. It has been found that ANN modelling approach could effectively represents the relationship between these fabric properties and performance under steam exposure.…”
Section: Characterization and Modeling Of Thermal Protective Performance Of Polymeric Textile Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, multiple linear regression (MLR) and/or artificial neural network (ANN) models were developed by employing the identified key fabric properties to conveniently predict their performance. For example, a group of researchers [ 21 , 22 , 23 , 24 , 25 ] found that weight, thickness, and thermal and evaporative resistance are the key fabric properties that affect the fabric’s thermal protective performance. On the other hand, these researchers concluded that the thermo-physiological comfort performance is mostly affected by fabric weight, evaporative resistance, and water spreading properties.…”
Section: Introductionmentioning
confidence: 99%
“…Необхідність вимірювання фізичних властивостей тканин; а також теплозахисні характеристики тканин оцінювали під впливом вогню, отриманого в результаті лабораторного моделювання коктейлю Молотова [8]. Ефективність розраховувалась за кількістю теплової енергії, що передається через тканини; крім того, час, необхідний для отримання опіку другого ступеня на тілах носіїв, прогнозували з розрахункової переданої теплової енергії.…”
unclassified